Cryoballoon pulmonary vein isolation as a standard approach for interventional treatment of atrial fibrillation. A review and a practical guide to an effective and safe procedure - Kiełbasa, Grzegorz; Jastrzębski, Marek (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
Since the cryoballoon was introduced into clinical practice, approximately half a million patients have undergone a pulmonary vein isolation (PVI) using this tool throughout the world. This single-shot technique makes the pulmonary vein isolation procedure easier and has the potential to expand access to the interventional treatment of atrial fibrillation (AF), eventually leading to a reduction of the AF-related disease burden. Several studies and metanalyses have assessed the acute and long-term efficacy of cryoballoon-based PVI. The reported success rate of PV isolation during the procedure is about 98%. Despite this, the long-term effectiveness of the procedure (AF free survival) assessed at 1 year after the ablation is in the range of 70–82%. The AF-free survival rate significantly depends on the clinical characteristics of the studied group and the presence of risk factors, especially the type of AF (paroxysmal vs. persistent), LA size and the presence of heart failure. For a safe and effective procedure the electrophysiologist should be aware of all minute details of the procedure including several tricks developed by the most experienced operators and the pre-procedural and post-procedural management recommendations. Detailed knowledge of complications of cryoballoon (CB)-based ablation is mandatory. This review concentrates on the practical aspects and recommendations for a cryoballoon ablation procedure. The review is based on the authors’ experience, including 800 procedures performed over 11 years with a low complication rate, and is presented within the context of the literature.